Evaluasi Pemanfaatan Laboratorium Biologi SMAN/MAN se-kecamatan Godean - Tri Erna Romadhoni; Much. Fuad Saifuddin (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
The laboratory has an important role in the implementation of learning, especially in the form of practicum. The use of school laboratories needs to be evaluated as a form of running school management. This study aims to determine: 1) the Principal's carrying capacity (contexts); 2) Resources support (input); 3) Laboratory utilization and constraints (process); 4) The percentage of students' interest in studying in the laboratory (product). This evaluation research uses the context, input, process, and product (CIPP) model. The research subjects were school principals, laboratory heads in SMA/MA Negeri in Godean sub-district, laboratory assistants at SMA N 1 Godean, two biology teachers from each school, and students SMA N 1 Godean 89 people and MAN 1 Sleman 80 people using proportionate stratified random sampling. The research object is the use of biological laboratories. Data collection techniques used are observation, interviews, questionnaires, and documentation. The data analysis technique used is in the form of qualitative and quantitative descriptive analysis. The evaluation results by CIPP obtained: 1) Context, the support capacity provided by the Principal by facilitating laboratory utilization activities; 2) Input, the availability of infrastructure suggestions is used to support learning through practicum and demonstrations. Management is carried out by laboratory personnel. Management includes planning, arrangement, arrangement, monitoring, and evaluation; 3) Process, the laboratory is used based on its function. The obstacles faced are infrastructure, limited time, and human resources; 4) Product, the percentage of student interest in learning in the laboratory of SMA N 1 Godean is 94.01% and MAN 1 Sleman is 91.39%.